KONSEP DAN CIRI-CIRI FIQH LESTARI: KE ARAH MENGARUSPERDANAKAN FIQH DALAM KEHIDUPAN MASYARAKAT - Abdullah, Atikullah (Jurnal Syariah, 2010)
In term of its nature, fiqh has always been misconstrued as either too rigid and stagnant based solely on the classical fiqh literature, or too open and flexible based on the boundless changes in the life of humans and their system of values. As a result, the importance of fiqh in human life has been frequently played down, either because fiqh is considered as out of date and irrelevant to the demands of the dynamic modern life or because it is viewed that every change that occurs in our system of values is the result of the changes in the system of life that are inherently consonant with the rules of Islamic fiqh. Therefore, this paper will aim to prove that the nature of Islamic fiqh is based on the numerous principles that ensure its sustainability to continuously guide human beings towards a dynamic life in different circumstances, places and times. It is concluded that Islamic fiqh has always been more than being able to provide guidelines to human beings in all circumstances in order to achieve a just and harmonious system, thus, ensuring the sustainability of human life.